1995
DOI: 10.1042/cs0890533
|View full text |Cite
|
Sign up to set email alerts
|

The Urinary F1 Activation Peptide of Human Prothrombin is a Potent Inhibitor of Calcium Oxalate Crystallization in Undiluted Human Urine in Vitro

Abstract: 1. The urinary F1 activation peptide of prothrombin is the predominant protein incorporated into calcium oxalate crystals precipitated from human urine. The aim of this study was to examine the effect of pure urinary prothrombin F1 on calcium oxalate crystallization in human urine. 2. Urinary prothrombin F1 was purified from demineralized calcium oxalate crystals precipitated from human urine, and its effects on calcium oxalate crystallization induced by addition of an oxalate load were tested in undiluted, ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 24 publications
(52 reference statements)
8
70
0
Order By: Relevance
“…PF1 and BK are potent inhibitors of CaOx crystal growth (3,4,38), and can be produced in the kidney (30,42). While the entire ITI molecule has been shown to inhibit CaOx crystallization (9), the heavy chain components do not have inhibitory activity, and BK is thought to be responsible for the ability of ITI to inhibit CaOx crystallization (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PF1 and BK are potent inhibitors of CaOx crystal growth (3,4,38), and can be produced in the kidney (30,42). While the entire ITI molecule has been shown to inhibit CaOx crystallization (9), the heavy chain components do not have inhibitory activity, and BK is thought to be responsible for the ability of ITI to inhibit CaOx crystallization (21).…”
Section: Discussionmentioning
confidence: 99%
“…Such proteins include TammHorsfall protein (THP) (20), osteopontin (uropontin) (2), prothrombin fragment 1 (PF1) (38), inter-␣-trypsin inhibitor (ITI) (9), and bikunin (BK), a portion of ITI (3), calgranulin (34), CD59 (7), and albumin (10). Although some reports suggest defects, deficiencies, or variations of these molecules among SF vs. normal subjects (13,14,26,27,43), it remains unclear whether any of these is a cause or a consequence of stones; no research thus far has translated molecular knowledge into clinical practice.…”
mentioning
confidence: 99%
“…2,13 There are many reports about the proteins extracted from human urine and the matrices of urinary stones which exhibit inhibitory activity on calcium oxalate crystal nucleation, growth, and aggregation. 4,5,14,15 Nephrocalcin is a known glycoprotein which exhibits a strong inhibitory effect on nucleation, growth, and aggregation of COM crystals. 16 Recently, it has been reported that these substances also have some effect on crystal-cell interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have focused our attention on purification, identification and functional analysis of a novel CaOx crystal growth inhibitor and on its potential role in the pathogenic mechanisms of nephrolithiasis. Currently known stone inhibitory proteins are nephrocalcin (22), TammHorsfall protein (23), uropontin (24), inter-α-trypsin inhibitor (bikunin) (25), and urinary prothrombin fragment 1 (crystal matrix protein) (26). Interestingly, these stone inhibitors have similar physical and chemical properties; they are small anionic proteins that bind to calcium and inhibit either growth or aggregation of CaOx crystals.…”
Section: Introductionmentioning
confidence: 99%